Breaking an image encryption algorithm based on chaos - Li, Chengqing; Chen, Michael Z Q; Kwok-Tung Lo (arXiv.org, 2016)
Recently, a chaos-based image encryption algorithm called MCKBA (Modified Chaotic-Key Based Algorithm) was proposed. This paper analyzes the security of MCKBA and finds that it can be broken with a differential attack, which requires only four chosen plain-images. Performance of the attack is verified by experimental results. In addition, some defects of MCKBA, including insensitivity with respect to changes of plain-image/secret key, are reported.